Genotype-phenotype associations in patients with hypertrophic cardiomyopathy and mutations in the troponin T gene - Morgado, Sofia Videira Begonha Sequeira (2022)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2021